112k views
1 vote
16x² -9 = 4ײ + (4x²+9)

User Vlumi
by
5.7k points

1 Answer

4 votes

For this case we must solve the following equation:


16x ^ 2-9 = 4x ^ 2 + (4x ^ 2 + 9)

We remove the parentheses on the right side:


16x ^ 2-9 = 4x ^ 2 + 4x ^ 2 + 9

We add similar terms on the right side:


16x ^ 2-9 = 8x ^ 2 + 9

We subtract
8x ^ 2from both sides of the equation:


16x ^ 2-8x ^ 2-9 = 9\\8x ^ 2-9 = 9

We add 9 to both sides of the equation:


8x ^ 2 = 9 + 9\\8x ^ 2 = 18

We divide by 8 on both sides of the equation:


x ^ 2 = \frac {18} {8}\\x ^ 2 = \frac {9} {4}

We apply square root to both sides of the equation:


x = \pm \sqrt {\frac {9} {4}}

We have two roots:


x_ {1} = \frac {3} {2}\\x_ {2} = - \frac {3} {2}

Answer:


x_ {1} = \frac {3} {2}\\x_ {2} = - \frac {3} {2}

User Random Student
by
5.6k points